Rebel music race, empire, and the new Muslim youth culture - Aidi, Hisham (Pantheon Books, 2014)
Hisham Aidi examines the secular and religious movements that have recently emerged among Muslim youth in the West as a means of protest against the policies of the War on Terror. In all, Aidi has written a riveting, eye-opening portrait of a growing, potentially radical segment of the global youth culture.